Hybrid microwave processing of particulate materials using a novel non-conventional fluidised bed - Morona Murillo, Lorena (2023)
Microwave technologies have been widely used in various industries for heating applications, offering several benefits when compared to other conventional systems including faster heating rates, selective and volumetric heating, instantaneous control over energy delivery and the potential to be powered by a sustainable energy source. However, challenges arise when it comes to higher temperature industrial processing (exceeding ~100 ºC). Achieving heating homogeneity and uniform material treatment remains a notable issue and the requirement for bespoke designs often leads to expensive equipment and materials of construction. Most of the existing techniques to overcome those challenges rely on the complexity of the use of moving parts. Microwave fluidised-bed reactors have been subject to extensive research for their use in industrial applications, primarily due to their advantageous particle mixing capabilities, accompanied by the rapid and efficient heating provided by microwave energy. Nonetheless, these systems still have limitations, including reactor tube fragility, potential overheating, and limited overall robustness. A novel hybrid microwave toroidal fluidised-bed system, TorWave reactor, was developed collaboratively by the University of Nottingham and Torftech Ltd. to address the mentioned challenges when it comes to scaling up microwave processors.